ANALISIS PEMBUKTIAN DALAM SENGKETA PERDATA MENGENAI WANPRESTASI DALAM PERJANJIAN - Komang Rama Agastya (Semarang Law Review (SLR), 2025)
This article analyzes the evidence in civil disputes concerning breach of contract, which arises when obligations are not fulfilled. Evidence plays a crucial role in substantiating claims in court. The rules governing the burden of proof, the categories of admissible evidence, and the judge’s evaluation of such evidence are all part of the issues addressed. The purpose of this research is to protect the rights and responsibilities of the parties involved, ensure an efficient legal system, and assess the evidence in contractual disputes. The research employs a normative legal method through statutory analysis. Written documents, witnesses, oaths, confessions, and presumptions are all examples of evidence. The plaintiff must demonstrate the defendant’s negligence. The court evaluates both the strength and the credibility of the evidence. The aim of this analysis is to ensure a fair trial. Achieving material truth and substantive justice requires an understanding of the burden of proof and the methods of evaluating evidence.   Abstrak Artikel ini menganalisis pembuktian dalam sengketa perdata terkait wanprestasi dalam perjanjian, yang terjadi ketika kewajiban tidak terpenuhi. Pembuktian krusial untuk membuktikan dalil-dalil di persidangan. Rumusan masalah meliputi pengaturan beban pembuktian, jenis alat bukti yang diakui, dan penilaian hakim terhadap bukti. Tujuan penelitian adalah menganalisis pembuktian dalam sengketa wanprestasi, memastikan proses peradilan yang efektif, serta melindungi hak dan kewajiban pihak-pihak. Metode penelitian adalah hukum normatif, menganalisis peraturan perundang-undangan. Alat bukti meliputi dokumen tertulis, saksi, persangkaan, pengakuan, dan sumpah. Penggugat harus membuktikan kelalaian tergugat. Pengadilan menilai keabsahan dan kekuatan bukti. Analisis ini bertujuan memastikan peradilan yang adil. Pemahaman beban pembuktian dan penilaian bukti penting untuk mencapai kebenaran materiil dan keadilan substantif.